Psychological, Behavioral, and Interpersonal Effects and Clinical Implications for Health Systems of the Coronavirus (COVID-19) Pandemic: A Call for Research - Castelnuovo, Gianluca; De Giorgio, Andrea; Manzoni, Gian Mauro; Treadway, Darren C.; Mohiyeddini, Changiz (Frontiers in Psychology, 2020)
COVID-19 emerged at the end of 2019 and was classified as a pandemic by the WHO on 11 March 2020. Both the COVID-19 emergency and the extraordinary measures to contain it have negatively affected the life of billions of people and have threatened individuals. One of the main goals of clinical and health psychology during this pandemic is to investigate behavioral, cognitive, emotional, and psychobiological responses to the COVID-19 emergency as well as to the preventive measures that have been imposed by governments to limit the contagion, such as social isolation. Psychological research has the responsibility to deliver sound empirical evidence to inform public health policies, and to support and advise governments and policy makers in their introduction of sustainable, feasible and cost-efficient prevention and intervention guidelines. Hence, the goal of this call for research is to stimulate theoretical discussions and empirical investigations on the bio-psycho-social impacts of COVID-19 for individuals, groups and nations. We invite contributions that address challenges that the COVID-19 emergency has imposed on couples, families and social systems. In addition, we call for studies that assess the specific effects of the COVID-19 on highly vulnerable populations such as children, adolescents, pregnant women, patients suffering from chronic and life threatening conditions, health care workers and elderly citizens. Papers focusing on the impact of emotion regulation and coping strategies are encouraged. Original Research, Data Reports, Study Protocols, Single Case Reports and Community Case Studies, Theoretical Perspectives and Viewpoints are invited to help improve our understanding of the COVID-19.